Suture-based vs. pure plug-based vascular closure devices for VA-ECMO decannulation–A retrospective observational study - Scherer, Clemens; Theiss, Hans; Istrefi, Mario; Binzenhöfer, Leonhard; Kupka, Danny; Stocker, Thomas; Lüsebrink, Enzo; Stambollxhiu, Era; Alemic, Ahmed; Petzold, Tobias; Stark, Konstantin; Deseive, Simon; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) is a valuable treatment option for patients in cardiogenic shock, but complications during decannulation may worsen the overall outcome. Therefore, the aim of this study was to compare the efficacy and safety of suture-based to pure plug-based vascular closure devices for VA-ECMO decannulation. Methods In this retrospective study, the procedural outcome of 33 patients with suture-based Perclose ProGlide closure devices was compared to 38 patients with MANTA plug-based closure devices. Results Rate of technically correct placement of closure devices was 88% in the suture-based group and 97% in the plug-based group (p = 0.27). There was a significant reduction of severe bleeding events during VA-ECMO decannulation in plug-based versus suture-based systems (3% vs. 21%, p = 0.04). Ischemic complications occurred in 6% with suture-based and 5% with plug-based device (p = 1.00). Pseudoaneurysm formation was detected in 3% in both groups (p = 1.00). No switch to vascular surgery due to bleeding after decannulation was necessary in both groups. Conclusion Based on our retrospective analysis, we propose that plug-based vascular closure should be the preferred option for VA-ECMO decannulation. This hypothesis should be further tested in a randomized trial.